Flaw characterization and correlation with cracking strength in Engineered Cementitious Composites (ECC). (May 2018) - Lu, Cong; Li, Victor C.; Leung, Christopher K.Y.
Abstract: Engineered Cementitious Composite (ECC) is a class of fiber reinforced composites showing strain hardening behavior. The variation of cracking strength among various sections of a tensile specimen is a key factor governing the cracking behaviors of ECC. This study employs X-ray computed tomography method to investigate the correlation between cracking strength and flaw distribution in ECC, and identifies the dimensions of pre-existing flaws to be the main influencing parameters. Specifically, the largest cross-sectional area of a flaw perpendicular to stress can be well correlated with cracking strength. To validate the observation, the classic model on first crack strength is modified in this study by adopting a refined fiber bridging relation and employing iterated crack profile. The simulated cracking strength vs flaw size relation is in good agreement with test results. This study provides an improved understanding of the multiple cracking mechanism in ECC, which is useful for material design.